Implementation of Islamic Business Ethics and Preparation of Financial Statements for Muslim Entrepreneurs in Sidoarjo City - Sri Wahyuni; Sigit Hermawan (Indonesian Journal of Islamic Studies, 2022)
This study aims to determine the suitability between the implementation of business ethics and the preparation of financial statements at the Nursyifa Pharmacy Sidoarjo with Islamic business ethics. This type of research is qualitative with a case study method, data is collected by conducting literature studies, observations and in-depth interviews with informants including owners, employees and consumers of Apotek Nursyifa who are determined using judgment techniques then the collected data is analyzed using qualitative descriptive data analysis methods. The results of this study indicate that Nursyifa Pharmacy implements Islamic business ethics in business activities and financial statement preparation well, although not perfectly. The imperfection of the implementation of Islamic business ethics at the Nursyifa Pharmacy Sidoarjo lies in the employee dress policy applied and the involvement of conventional banks in transactions carried out with distributors that are not in accordance with Islamic law.